(untitled) (Journal of Educational Sciences, 2023)
The article considers the introduction of the still insufficiently studied updated content of education in the educational process of secondary schools. The special importance of interdisciplinary connections has been scientifically substantiated for the purpose of effective assimilation by students of one or another content. The scientific and methodological foundations of the updated program are analyzed, the priorities of which are spiritual, cultural and moral values in the education of young people, the development of skills and ideas that give them confidence and success in such a rapidly changing world, the ability to apply the acquired knowledge in all kinds of life situations from the point of view of critical thinking. Within the framework of the article, the necessary pedagogical conditions obtained as a result of the integration of the subjects of primary school subjects are determined. Along with this, guidelines have been prepared not only for primary school teachers, but also for all teachers leading the educational process according to the updated program. According to the results of world studies in the field of education, it is stated that teachers with a high level of professionalism will be able to improve the knowledge of young people in terms of quality. On the topic of the study, analysis, sorting, questioning, interviews, diagnostics, and a pedagogical experiment were carried out. The methods of conducting mathematical and statistical processing on them are comprehensively applied. The developed system of conditions was tested in experimental and pedagogical work, in which 84 schoolchildren took part on the basis of the N5 school-gymnasium named after Zhambyl Zhabaev in Taraz. Key words: interdisciplinary connections, updated program, pedagogical requirements, conditions, elementary class, teacher, modeling.